Supply chain strategy : the logistics of supply chain management - Frazelle, Edward (McGraw-Hill's AccessEngineering., 2002)
"Supply Chain Strategy" is today's most comprehensive resource for up-to-the-minute thinking and practices on developing supply chain strategies that support a company's overall objectives. Covering world-class practices and systems, taken from the files of Coca-Cola, Wal-Mart, General Electric, and other companies, it covers essential supply chain subjects including: logistics data mining - for identifying the root cause of material and information flow problems, pinpointing opportunities for process improvements, and providing an objective basis for project-team decision making; and, inventory planning and management - presenting metrics, processes, and systems for forecasting, demand planning, and inventory control, yielding lower inventory levels and improved customer service. It also covers: logistics information systems and Web-based logistics - helping to substitute information for inventory and work content; transportation and distribution - for connecting sourcing locations with customers at the lowest cost by, among other things, leveraging private and third-party transportation systems; and, logistics organization development - including the seven disciplines that link enterprises across the supply chain, as well as logistics activities within those enterprises.